Memória organizacional e a constituição de bases de conhecimento - Molina, Letícia Gorri [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
With the rapid development of society, the result of the constant growth of distinct areas, small and medium sized enterprises needed to develop mechanisms that would help in their own development, aiming at the survival in a competitive world. One of the ways found by these companies was the structuring of urban industrial and business, focused on the same business segment, called local productive arrangements. In this scenario, the role of organizations such as protagonists of an environment that is characterized by an extensive informational production is highlighted, and which needs to be organized and dealt with, with the objective to facilitate access and use. Distinct informational content has been produced by the organizations, however much of the content has been lost. This may be the result of the lack of mechanisms that can manage and preserve them effectively for future access and dissemination. According to this scenario, there arises the need to study and analyze the importance of creating a structure of organizational memory, which will allow for the record, the preservation and dissemination of knowledge that has been produced by the participants by the participants of Local Productive Arrangement of Information Technology of Londrina and region. As a general objective of the study it was intended to examine how organizational memory constitutes corporate spaces, specifically in local clusters, having as focus the importance of access to and use of information, allowing the management of knowledge produced. As research methods, were used the Case Study that according to Yin (2005) and a search strategy focused on the knowledge of individual phenomena, organizational and group, among others, is the Content Analysis of Laurence Bardin... (Complete abstract click electronic access below)

Com o acelerado desenvolvimento da sociedade, resultado do constante crescimento de distintas áreas, as pequenas e médias empresas precisaram desenvolver mecanismos que as ajudassem no seu próprio desenvolvimento, visando à sobrevivência no mundo competitivo. Uma das maneiras encontradas por essas empresas foi a estruturação de aglomerações empresariais e industriais, voltadas ao mesmo segmento de negócio, denominada de arranjos produtivos locais. Nesse cenário, evidencia-se o papel das organizações como protagonistas de um ambiente que se caracteriza por uma extensa produção informacional, que precisa ser organizada e tratada, com objetivo de facilitar seu acesso e uso. Distintos conteúdos informacionais têm sido produzidos pelas organizações, entretanto muitos conteúdos têm se perdido. Isso pode ser resultado da inexistência de mecanismos que possam gerenciá-los e preservá-los eficazmente para o futuro acesso e disseminação. De acordo com esse panorama, surge a necessidade de se estudar e analisar a importância da criação de uma estrutura de memória organizacional, que possibilite o registro, a preservação e a disseminação do conhecimento que tem sido produzido pelos participantes do Arranjo Produtivo Local de Tecnologia de Informação de Londrina e região. Como objetivo geral do trabalho, pretendeu-se analisar de que maneira a memória organizacional se constitui em espaços empresariais, especificamente em arranjos produtivos locais, tendo como enfoque a importância do acesso e uso da informação, possibilitando o gerenciamento do conhecimento produzido. Como métodos de pesquisa, utilizaramse o Estudo de Caso que segundo Yin (2005) é uma estratégia de pesquisa voltada ao conhecimento de fenômenos individuais, organizacionais e de grupo, entre outros, e a Análise de Conteúdo de Laurence Bardin...
Keywords: Desenvolvimento organizacional; Gerenciamento da informação; Arranjos produtivos locais